ANALISIS TINGKAT EFEKTIVITAS PEMBERIAN KREDIT DI BANK BPR CABANG TANGERANG - Tito Inneka Widyawati (Universitas Muhammadiyah Tangerang, 2018)
This study aims to determine the level of effectiveness of lending by PT. BPR Tangerang Branch.The type of research used is quantitative descriptive. Data collection techniques are carried out through observation, questionnaires, interviews and documentation. Determination of respondents was chosen by using purposive sampling with a sample of 70 respondents. The data analysis technique used is statistical analysis.The results showed that the level of attainment of the percentage of the effectiveness of giving credit as a whole is in the effective category (82.75 percent), thus it can be said that the credit given by Bank PT. BPR Tangerang Branch is effective seen from the 5C principle, namely Character, Capacity, capital, Collateral, and conditon of economic. Judging from the results of the measurement of the Characteristics of lending effectiveness through its dimensions shows that all dimensions support the effectiveness. Judging from the table above 1 dimension is in the very effective category, namely the Character dimension 86.93%, 4 dimensions are in the effective category, namely the dimensions of Capacity 78.14%, capital 82.86% and dimensions of Collateral 84.86%, and dimensions condition of economy is 74.71%.